Early handwriting development: a longitudinal perspective on handwriting time, legibility, and spelling - Lidia Truxius; Judith Sägesser Wyss; Michelle N. Maurer; Michelle N. Maurer (Frontiers in Psychology)
IntroductionLearning to write is a complex task involving peripheral (e.g., handwriting speed and legibility) and central (e.g., spelling) processes. Coordinating these processes is particularly demanding for novice writers who have not yet automated their handwriting skills. To better support children in developing handwriting, it is crucial to understand the development and interactions of these peripheral and central processes over time.MethodsThis longitudinal study (n = 363; 49.8% girls) investigated the development and interrelations of handwriting speed (time spent on writing tasks), legibility, and spelling in German-speaking first-grade children (Mage = 7 years) across 12 months. The children were assessed at three time points, spaced 6 months apart, from the beginning of the first grade to the start of the second grade.Results and discussionWhile performance in all domains of handwriting (time, legibility, and spelling) improved over the school year, these skills were particularly strongly interrelated at the beginning of writing acquisition but became increasingly independent towards the second grade. Surprisingly, the results from the structural equation model showed that the relations between handwriting legibility and time reversed over time: Initially, faster handwriting was associated with more legible handwriting, while with increasing practice a trade-off appeared. Furthermore, when considering cross-lagged paths, the structural equation model revealed that handwriting legibility at the beginning of the first grade significantly predicted subsequent handwriting time and spelling abilities at the end of the school year. In summary, handwriting proficiency stabilizes quickly, while patterns of associations between peripheral and central handwriting processes change across the first year of handwriting instruction.